Development of a Teaching Model for Saxophone Skill 1 College of Music at Bansomdejchaopraya Rajabhat University - Sisiadngam, Warinthorn (Rangsit Music Journal, 2024)
The objectives of this research is 1) To develop of teaching model of saxophone Skill 1 2) to compare the achievement of knowledge and saxophone musical skills 1, pre-test and post-test after having been studied according to the model of saxophone skills 1 created by the researcher and 3) to study the satisfaction towards the teaching style of Saxophone Skills 1. The research method is experimental research. The population used in the research was 1st year students in Bachelor of Education Program in Western Music Education and Bachelor of Music Program in Western Music, College of Music at Bansomdejchaopraya Rajabhat University, who studies in in Semester 1, Academic Year 2022 total 7 people. The results of the research were as follow:1) the model of teaching model of saxophone Skill 1 that developed was consisting of 6 major components: (1) principles and rationale, (2) objectives, (3) content, (4) teaching and learning activities, (5) learning materials, and (6) measurement and evaluation. 2) knowledge achievement and saxophone musical skills 1 of students who practice the saxophone found that the average score from the knowledge test and music skills before and after the experiment was a statistically significant difference at the .05 level ( = 49.29and SD = 2.407) 3) The average of the satisfaction with the teaching model of saxophone Skill 1 was at the highest level ( = 4.71, SD = 0.46).